Labeling of virus components for advanced, quantitative imaging analyses - Sakin, Volkan; Müller, Barbara (FEBS letters, 2016)
In recent years, investigation of virus-cell interactions has moved from ensemble measurements to imaging analyses at the single-particle level. Advanced fluorescence microscopy techniques provide single-molecule sensitivity and subdiffraction spatial resolution, allowing observation of subviral details and individual replication events to obtain detailed quantitative information. To exploit the full potential of these techniques, virologists need to employ novel labeling strategies, taking into account specific constraints imposed by viruses, as well as unique requirements of microscopic methods. Here, we compare strengths and limitations of various labeling methods, exemplify virological questions that were successfully addressed, and discuss challenges and future potential of novel approaches in virus imaging.
Gesehen am 12.02.2019